Bienestar económico provincial en Ecuador, año 2018 - Rocano Dominguez, Jimmy Leonardo (2022)
The study of economic welfare is a matter of great relevance for the implementation of public policy. In this case, the traditional way of measuring economic well-being, using only income, has become obsolete. For this reason, this research calculates the provincial economic well- being index (IBE) in Ecuador for the year 2018. Using the Data Envelopment Analysis (DEA), the index is obtained for 23 Ecuadorian provinces, the weights of the components of the index and graph. The results of the DEA reflect that there are 3 groups of provinces; the first group with an IBE equal to unity, the second group with values close to unity and the third group with low well-being indices. In statistical terms, it is confirmed that the provinces have a heterogeneous level of well-being. In addition, the results of the disaggregation of weights indicate that each of the provinces weight the components depending on their socioeconomic conditions. Graphically, it was possible to determine that the Amazon region encompasses the provinces with the lowest IBE. The results reaffirm that public policies should be focused on certain provinces and on certain socioeconomic variables to favor provincial economic well- being.